Determinants and consequences of executive compensation-related shareholder activism and say-on-pay votes: A literature review and research agenda. Issue 1 (10th February 2018) - Obermann, Jörn; Velte, Patrick
Abstract : This systematic literature review analyses the determinants and consequences of executive compensation-related shareholder activism and say-on-pay (SOP) votes. The review covers 71 empirical articles published between January 1995 and September 2017. The studies are reviewed within an empirical research framework that separates the reasons for shareholder activism and SOP voting dissent as input factor on the one hand and the consequences of shareholder pressure as output factor on the other. This procedure identifies the five most important groups of factors in the literature: the level and structure of executive compensation, firm characteristics, corporate governance mechanisms, shareholder structure and stakeholders. Of these, executive compensation and firm characteristics are the most frequently examined. Further examination reveals that the key assumptions of neoclassical principal agent theory for both managers and shareholders are not always consistent with recent empirical evidence. First, behavioral aspects (such as the perception of fairness) influence compensation activism and SOP votes. Second, non-financial interests significantly moderate shareholder activism. Insofar, we recommend integrating behavioral and non-financial aspects into the existing research. The implications are analyzed, and new directions for further research are discussed by proposing 19 different research questions.